1981
DOI: 10.1002/ddr.430010307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on isolation stress‐stimulated carcinogen‐metabolizing enzymes of rats

Abstract: Rats aged 6, 12, 24, 36, and 52 weeks were subjected to social isolation for 4 days, while littermates housed in groups of six for the same period served as controls. The isolation treatment resulted in a 2-fold increase in the serum corticosterone level of all except the youngest animals in whom the hormone level was greater than 4 times that of their agematched controls. Hepatic rnicrosomal protein was highest in the 24-week-old rats and lowest in the rats aged 52 weeks. The levels of most of the enzymes mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Therefore, in the present experiment the stress-induced elevations in lipoperoxide and decreased GSH levels occurred, predictably, in the liver. Previous reports have indicated that the susceptibility of the P450-dependent oxidases to stress is influenced by a number of factors, in particular the age of the subject (Capel et al, 1981;Rikans and Notley, 1982). Younger animals also have greater resistance to lipoperoxide formation (Sharma, 1977;Player et al, 1977) and have higher GSH levels in many tissues (Abraham et al, 1978).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, in the present experiment the stress-induced elevations in lipoperoxide and decreased GSH levels occurred, predictably, in the liver. Previous reports have indicated that the susceptibility of the P450-dependent oxidases to stress is influenced by a number of factors, in particular the age of the subject (Capel et al, 1981;Rikans and Notley, 1982). Younger animals also have greater resistance to lipoperoxide formation (Sharma, 1977;Player et al, 1977) and have higher GSH levels in many tissues (Abraham et al, 1978).…”
Section: Discussionmentioning
confidence: 97%
“…However, GSH levels also decrease with increasing age (Abraham et al, 1978). In addition, differences in the "susceptibility to stressful stimuli," resulting in quantitative differences in metabolic response, have been observed in animals of differing ages (Capel et al, 1981;Rikans and Notley, 1982). Thus, the present study was conducted with groups of rats of differing ages within the range most commonly employed in previous investigations.…”
Section: Introductionmentioning
confidence: 95%
“…Several pathways exist for enzyme-catalyzed xenobiotic biotransformation in the liver, and these pathways are modulated by a large number of environmental and hormonal factors. Among the factors which modulate cytochromes CYP and other drug-metabolizing enzymes are psychological or physiological stress (7)(8)(9). It is noteworthy that animals exposed to conditions of psychological or physiological stress are vulnerable to different pathogenic factors such as the reactive derivatives of drugs, which can stimulate mutagenic or carcinogenic processes (10).…”
Section: Introductionmentioning
confidence: 99%